REFLEJO, diseño de libro ilustrado sobre la cultura peruana y japonesa - Castillo Sotomayor, Hernan (2022)
Reflection is a binational graphic exhibition that reveals the great cultural similarities between Japan and Peru through the comparison and graphic analysis of various elements belonging to the heritage of these countries located on opposite sides of the planet. The means by which the theme to be developed is expressed is a book in letter format, made up of illustrations created by the authors themselves, deepened with information and other formats such as poems, for example, that help the reader to delve into these elements and the similarities that they address. Each pair of elements is located at each end of the book once opened, these are united by a single statement that is applicable to both elements, this in order to show the similarities between them. On the pages following the elements, the reader can find information, compiled from various sources, about the elements to make clear the similarity that exists between them and also their importance in the culture to which they belong.